The Effect of Project Based Learning Model on Student Satisfaction - Fitria; Emy Iryanie (International Journal of Integrative Research, 2023)
Advances in learning media technology, previously in the form of visual and audio displays, can now be put together in multimedia. The data analysis used in this research was regression analysis. This research aims to be a consideration in the application of methods to learning. The first data analysis in this study was to test the quality of the data. The second data analysis involved testing the classical assumptions. The third was to test multiple linear regression analysis to determine the Goodness of Fit Model to show whether the regression model formed is feasible or not to be used to predict the dependent variable. In several tests that have been carried out, the PBL method variable in the learning process variable in the course has an effect on student satisfaction, which means that the model used in this study is feasible.